Assessment of Chemical Compounds for in vitro and in vivo Activity against Bacterial Black Spot of Mango - Shivakumar P. Banakar.1, Naveenkumar, K.J.1 and M. Krishnappa2, Thirumalesh, B.V.1, Thippeswamy, B1*., (Recent Research in Science and Technology, 2011)
Bacterial black spot of mango caused by Xanthomonas campestris pv. mangiferaeindicae (Xcm) produces considerable economic losses in many parts in india. The extent to which bactericides control this disease effectively is low. In this study the bactericidal effect of different products was assessed in vitro and in vivo in mango plants under greenhouse conditions. Thirteen antibacterial substances, one commercial formulate and also combinations were tested. In vitro analysis showed that minimal inhibitory concentration (MIC) of antibacterial substances was between 2–8 µgml-1, except for copper sulphate with a MIC value of 100 µgml-1and Vancomycin, Amoxycillin which was not active at 1000 µgml-1. MIC values of commercial formulate bactrinashak ranged between 5 and 30 µgml-1, and combinations of ciprofloxacin + copper sulphate; ciprofloxacin + bactrinashak; ciprofloxacin + copper oxychloride, ciprofloxacin + tetracycline and tetracycline + bactrinashak, showed a great effect at sub-inhibitory concentrations. Treatments including copper sulphate and copper oxychloride significantly reduced disease symptoms on plants, whereas bacitracin was less effective, where as fluconozole and penicillin does not show any inhibition. In two different field trials, the percentage of leaves symptoms was lower, after treatment with copper sulphate combinations than in inoculated controls. These combinations of different antibacterial substances results were better than copper sulphate alone. We conclude that the combination of copper sulphate with ciproflaxacin may be useful in controlling symptoms of this disease in greenhouses.